2005
DOI: 10.1200/jco.2005.11.111
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Docetaxel in Patients With Hormone-Dependent Prostate-Specific Antigen Progression After Local Therapy for Prostate Cancer

Abstract: This study demonstrated the activity of docetaxel alone, without androgen ablation, in patients with PSA progression after completion of local therapy. Treatment with docetaxel in this population with early disease progression was well tolerated, biochemically active, and was not androgen ablative. Accrual to national phase III studies in early disease is now critical and should be strongly encouraged to determine the ability of early chemotherapy to improve survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 16 publications
0
11
1
1
Order By: Relevance
“…The differences shown in TTP and OS might be due to the fact that, patients in our study had more advanced disease when entering study. We found a mean PSA of 448 microgram/L at baseline, compared to mean PSA of 114 microgram/L in the B-arm of TAX 327, suggesting that patients receiving DGP had poorer prognosis [6,8,17]. In our study 98% had bone metastasis and 56% had visceral metastasis, whereas patients in the B-arm of Tax 327 patients had bone involvement in 90% of cases and visceral metastasis in 22% of cases [6].…”
Section: Discussioncontrasting
confidence: 44%
“…The differences shown in TTP and OS might be due to the fact that, patients in our study had more advanced disease when entering study. We found a mean PSA of 448 microgram/L at baseline, compared to mean PSA of 114 microgram/L in the B-arm of TAX 327, suggesting that patients receiving DGP had poorer prognosis [6,8,17]. In our study 98% had bone metastasis and 56% had visceral metastasis, whereas patients in the B-arm of Tax 327 patients had bone involvement in 90% of cases and visceral metastasis in 22% of cases [6].…”
Section: Discussioncontrasting
confidence: 44%
“…Thus, PSA induction due to calcitriol therapy may be a marker of cellular transformation to a more indolent phenotype. Further, the observed PSA increases may be due to a transient stress response seen in this and other therapies such as docetaxel (26). Last, more recent data have shown that the PSA protein has significant biological properties that may reduce tumor invasiveness.…”
Section: Discussionmentioning
confidence: 84%
“…Goodin et al [44] treated 25 men with 70 mg/M 2 every 3 weeks for eight planned cycles. PSA declined in 18 men without any signifi cant decline in serum testosterone levels.…”
Section: Chemotherapy For Biochemical Relapse After Defi Nitive Localmentioning
confidence: 99%